Cutaneous metastases of signet-ring cell colorectal adenocarcinoma - Rodrigues,André Petter (2012)
Colorectal cancer is a common malignancy in our clinical practice and it often evolves to a metastatic stage. Cutaneous dissemination, however, is a rare form of presentation of this disease. This study reports the case of a 38-year-old female patient that, even after neoadjuvant chemotherapy, presented cutaneous metastases of signet-ring cell colorectal adenocarcinoma. The malignancy proved to be extremely aggressive, without response to clinical therapy nor allowing surgical management, leading the patient to death about six months after the diagnosis.